Agile Objects. (3rd July 2017) - German, Senta; Harris, Jim
ABSTRACT: In this article, the authors argue that the art-historical canon, however it is construed, has little relevance to the selection of objects for museum-based teaching. Their contention is that all objects are fundamentally agile and capable of interrogation from any number of disciplinary standpoints, and that the canon of museum education, therefore, consists in the entire contents of the museum. The article seeks to define the quality of agility in objects and discusses the selection of materials for teaching on that basis. In order to sustain the development of object-based learning in university museums, the authors argue that it is necessary to train a cohort of teachers able to use objects imaginatively and well, and they outline a training course for faculty, Agile Objects, aimed at equipping them to do so.